REMEDIASI MISKONSEPSI PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN CORE TENTANG KALOR DI SMP - Noviliani Noviliani; Stepanus Sahala Sitompul; Hamdani Hamdani (Universitas Tanjungpura, 2022)
The purpose of study was to determine the effectiveness of remediation of misconceptions by using the Connecting, Organizing, Reflecting, and Extending (CORE) learning model to reduce the number of student who had misconceptions about heat at SMP Negeri 6 Sambas. The form of design was pre-experimental with one group pretest-posttest design. This study used a random sampling method in intac group involving 35 students of class VIIIA who were tested using a multiple-choice diagnostic test consisting of 9 questions. Based in data analysis, there was a decrease in the percentage of the students who experienced misconceptions with an average of 75.75%. The result of McNemar’s test shows that the calculated 2 of 28.26 is greater than 2 table of 3.84, so there is a significant conceptual change after remedial activities using the CORE model. The effectiveness of remediations based in the DQM price with an average of 83.27% (high category). The CORE model is expected to be used as an alternative to remediation activities to reduce the number of students who experience misconceptions.